ab/d + c = e for d

Discussion in 'Calculator Requests' started by math_celebrity, Oct 27, 2021.

  1. math_celebrity

    math_celebrity Administrator Staff Member

    ab/d + c = e for d

    I know this is a literal equation because we are asked to solve for a variable in terms of another variable

    Subtract c from each side to isolate the d term:
    ab/d + c - c = e - c

    Cancel the c's on the left side and we get:
    ab/d = e - c

    Cross multiply:
    ab = d(e - c)

    Divide each side of the equation by (e - c):
    ab/(e - c)= d(e - c)/(e - c)

    Cancel the (e - c) on the right side, and we get:
    d = ab/(e - c)

Share This Page